Drei Entdeckungen mit Hilfe von Software für Dynamische Geometrie (DGS) (mathematica didactica, 2005)
Working with dynamic geometry software in the geometry course in the in-service teacher training, the author discovered several facts from elementary geometry which were new to him. These facts will be presented in the article together with proofs in classical style.